Minimum wages and employment retention: A microeconometric study for Estonia. Issue 1 (2nd January 2018) - Ferraro, Simona; Hänilane, Birgit; Staehr, Karsten
ABSTRACT: This paper assesses the effect of increases in the Estonian minimum wage in 2013–2016 on the probability of workers at different wage levels retaining employment. The effect is identified by comparing the probability of workers remaining employed after increases in the minimum wage in 2013–2016 with the probability of workers at comparable wage levels remaining employed in the 2009–2011 when the minimum wage was left unchanged. Estimations on data from the Estonian Labour Force Survey show that the increases in the minimum wage in 2013–2016 had no or small and imprecisely estimated effects on employment retention for the directly affected workers and similarly for those indirectly affected. These results are robust to the choice of control variables, to refinements of the treatment group and to changes in the time sample.